Na tropie szamanizmu w paleolicie – na przykładzie jaskiń Cougnac i Pech-Merle . - Górzyński, Michał (Folia Praehistorica Posnaniensia, 2019)
The author of this thesis searches for traces of shamanism in paleolithic period through identification of signs and anthropomorphic resemblances that can have a connection with different stages of trance and shamanistic visions. For this article, Pech-Merle and Cougnac cave were chosen. Chronological range in this paper covers a period when Gravettian and Magdalenian cultures functioned. In order to carry out the above assumptions, the author used the results of structuralist research- search- ing for deep meaning and symbols, neuropsychological research – influence of altered states of con- sciousness on human and role of rites in simple societies, ethnographic research- different types of shamanic vocation and visions of shamanistic cosmology as well as interpretation of paintings and engravings based on the above mentioned scientific instruments. In the conclusion, the author shows that magical and religious practices similar to shamanism could function in paleolithic hunter-gatherer societies.